Effectiveness of Regional Financial Management in the Regional Government and Autonomy Bureau of the Regional Secretariat of Sumatera Province - Danda, Saskia Pratiwi; Asnil, Asnil; Erianjoni, Erianjoni; Syamsir, Syamsir (Journal of Economics and Management Scienties, 2025)
This study examines the effectiveness of regional financial management within the Bureau of Government and Regional Autonomy of the Regional Secretariat of West Sumatera Province. The research aims to evaluate the bureau’s fiscal governance performance and identify strategic priorities through SWOT analysis. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The analysis revealed that financial management practices have generally complied with existing regulations; however, several limitations persist, including fragmented coordination, low digital literacy, and uneven human resource capacity. Strengths lie in the presence of clear regulatory frameworks and committed leadership, while weaknesses are primarily related to outdated administrative processes. Opportunities arise from ongoing digital transformation initiatives and e-governance policies, whereas threats include rapid regulatory changes and economic instability. The findings suggest that strengthening digital readiness, leadership capability, and inter-departmental integration can significantly improve the bureau’s performance. This research contributes to the understanding of fiscal governance at the regional level and offers practical insights for policy reform and capacity development in decentralized public financial management systems.